Functionalization of polydimethylsiloxane membranes to be used in the production of voice prostheses - Ferreira, Paula Cristina Nunes (2018)
The voice is produced by the vibration of vocal cords which are located in the larynx. Therefore, one of the major consequences for patients subjected to laryngectomy is losing their voice. In these cases, a synthetic one-way valve set (voice prosthesis) can be implanted in order to allow restoration of speech. Most voice prostheses are produced with silicone-based materials such as polydimethylsiloxane (PDMS). This material has excellent properties, such as optical transparency, chemical and biological inertness, non-toxicity, permeability to gases and excellent mechanical resistance that are fundamental for its application in the biomedical field. However, PDMS is very hydrophobic and this property causes protein adsorption which is followed by microbial adhesion and biofilm formation. To overcome these problems, surface modification of materials has been proposed in this study. A commercial silicone elastomer, SylgardTM 184 was used to prepare membranes whose surface was modified by grafting 2-hydroxyethylmethacrylate and methacrylic acid by low-pressure plasma treatment. The hydrophilicity, hydrophobic recovery and surface energy of the produced materials were determined. Furthermore, the cytotoxicity and antibacterial activity of the materials were also assessed. The results obtained revealed that the PDMS surface modification performed did not affect the material's biocompatibility, but decreased their hydrophobic character and bacterial adhesion and growth on its surface.